Pancreas and gallbladder agenesis in a newborn with semilobar holoprosencephaly, a case report - Robert Hilbrands; Kathelijn Keymolen; Alex Michotte; Miriam Marichal; Filip Cools; Anieta Goossens; Peter In't Veld; Jean De Schepper; Andrew Hattersley; Harry Heimberg (BMC, 2017)
Abstract Background Pancreatic agenesis is an extremely rare cause of neonatal diabetes mellitus and has enabled the discovery of several key transcription factors essential for normal pancreas and beta cell development. Case presentation We report a case of a Caucasian female with complete pancreatic agenesis occurring together with semilobar holoprosencephaly (HPE), a more common brain developmental disorder. Clinical findings were later confirmed by autopsy, which also identified agenesis of the gallbladder. Although the sequences of a selected set of genes related to pancreas agenesis or HPE were wild-type, the patient's phenotype suggests a genetic defect that emerges early in embryonic development of brain, gallbladder and pancreas. Conclusions Developmental defects of the pancreas and brain can occur together. Identifying the genetic defect may identify a novel key regulator in beta cell development.